2007
DOI: 10.1177/000348940711601004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intracochlear New Bone and Fibrous Tissue Formation in Human Subjects with Cochlear Implants

Abstract: These preliminary results suggest that the degree of damage to the lateral cochlear wall may play an important role in influencing the amount of new tissue formation following cochlear implantation. Intracochlear new tissue does not appear to be an important determinant of performance as measured by word recognition scores or the total number of remaining spiral ganglion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
137
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 22 publications
16
137
2
5
Order By: Relevance
“…There are known potential problems with cochleostomy, such as perilymph loss and acoustic trauma caused by drilling, especially at the thickest part of the promontory. The bone dust, if present, may lead to the formation of new bone within the cochlea [Li et al, 2007]. There is also a risk of initiating osseous spiral lamina injury, because perilymph is toxic to hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are known potential problems with cochleostomy, such as perilymph loss and acoustic trauma caused by drilling, especially at the thickest part of the promontory. The bone dust, if present, may lead to the formation of new bone within the cochlea [Li et al, 2007]. There is also a risk of initiating osseous spiral lamina injury, because perilymph is toxic to hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the long-term presence of a foreign body (the electrode) in the ampulla, there was no evidence of acute or chronic inflammation in the labyrinth and only minimal new bone formation (Li et al 2007) was observed. The stable back-voltage measurements and single-pulse responses indicate that neither the conductivity of the tissues nor the efficacy of afferent nerve stimulation changed significantly during the course of the experiment.…”
Section: Effects Of Chronic High-frequency Electrical Stimulationmentioning
confidence: 98%
“…Damage to the cochlea during surgery, including insertion trauma and effects of drilling, can cause growth of bone and fibrous tissue (Fayad et al, 2009;Li et al, 2007;Somdas et al, 2007). This, in turn, can form regions of high impedance around the implant array, altering the pathway that current must take to activate the auditory nerve (Hanekom, 2005).…”
Section: Misplacement and Obstructed Current Pathsmentioning
confidence: 99%